7.4x-2.9=11.9

Simple and best practice solution for 7.4x-2.9=11.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7.4x-2.9=11.9 equation:


Simplifying
7.4x + -2.9 = 11.9

Reorder the terms:
-2.9 + 7.4x = 11.9

Solving
-2.9 + 7.4x = 11.9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2.9' to each side of the equation.
-2.9 + 2.9 + 7.4x = 11.9 + 2.9

Combine like terms: -2.9 + 2.9 = 0.0
0.0 + 7.4x = 11.9 + 2.9
7.4x = 11.9 + 2.9

Combine like terms: 11.9 + 2.9 = 14.8
7.4x = 14.8

Divide each side by '7.4'.
x = 2

Simplifying
x = 2

See similar equations:

| 1.95x-4.38z+2.83a-5.21z-9.27x= | | v+(v-16)+3(30-v)=641 | | 3a+4=24 | | h=32+14t-1+-16t | | -(6x+3)-(-5x-8)=3 | | (9-x)(3x+5)=0 | | -x-18+2x+4=6x+24 | | a-6b+2c+a-6b+n-2c= | | 9y+3=27 | | 4b+25=9b | | 6(4-1)-5(z+8)=16(z+1) | | y=-(1)-3 | | y=-(0)-3 | | y=-(-1)-3 | | 4b+5x=2x | | -8(t-5)-(t+4)=9 | | 2x+10=27 | | 7.7(-9+2x)=-49 | | y=6(5)-8 | | x=9x-12 | | y=6(1)-8 | | 12(2x-5)=24x+16 | | -(3y+2)-(-2y-8)=5 | | y=6(-1)-8 | | 6+2(x-1)=1-3(x-6) | | 4+6(x-2)=1-5(x-1) | | -49=3x+3x-7 | | -(4y+1)-(-3y-6)=4 | | 12+-2a=2 | | 9ln(8x)=54 | | 2y+10(2)=-16 | | 2y+10(-3)=-16 |

Equations solver categories